Legal Aspects of Business Contracts with the Threat of Punishment: Perspectives on the Protection of the Injured Party and Fairness of the Contract - Ibnu Juda Sembiring; Fauzan Hafizh; Wan Adrah Modana Barus; Mulia Aqsa Muhairir; Dollynoor Ilman (Jurnal Cendikia ISNU SU, 2024)
Business contracts are important legal instruments regulated by the Civil Code, particularly those related to agreements between parties in business activities. This study discusses various important aspects of business contracts, including the main components, forms of legal protection, the advantages and disadvantages of legality, elements of agreements, and the concept of force majeure. Based on Article 1320 of the Civil Code, a business contract must meet four valid requirements: agreement, capacity, a certain thing, and a lawful cause. Legal protection in business contracts is divided into two forms: preventive and repressive. Although the legality of business contracts provides various benefits such as legal certainty and protection for the parties, there are also several limitations such as costs, time, and unforeseen risks. In the context of force majeure, this condition can be a forgiving reason for debtors who cannot fulfill their obligations due to circumstances beyond their control. A thorough understanding of these aspects is important to create safe and sustainable business relationships within the applicable legal framework.